Catalytic Enantioselective Synthesis of anti‐Vicinal Silylboronates by Conjunctive Cross‐Coupling. Issue 22 (19th March 2020) - Meng, Yan; Kong, Ziyin; Morken, James P.
Abstract: Chiral 1, 2‐bimetallic reagents are useful motifs in synthetic chemistry. Although syn ‐1, 2‐bimetallic compounds can be prepared by alkene dimetallation, anti ‐1, 2‐bimetallics are still rare. The stereospecific 1, 2‐metallate shift that occurs during conjunctive cross‐coupling is shown to enable a practical and modular approach to the catalytic synthesis of enantioenriched anti ‐1, 2‐borosilanes. In addition to reaction development, the synthetic utility of anti ‐1, 2‐borosilanes was investigated, including applications to the synthesis of anti ‐1, 2‐diols and anti ‐1, 2‐amino alcohols Abstract : Vicinal dimetallics : Enantioselective catalytic conjunctive cross‐coupling reactions employing readily available silyl alkenyl boronic esters provide direct access to anti ‐vicinal silyl boronic esters. These compounds provide a versatile tool for the construction of 1, 2‐difunctional organic building blocks. Boc= tert ‐butoxycarbonyl; Bz=benzoyl; mac=dimethyl‐dihydroacenaphtho.